Pemilihan Rute Optimal Penjemputan Penumpang Travel Menggunakan Ant Colony Optimization Pada Multiple Travelling Salesman Problem (M-TSP) - Yosua Christopher Sitanggang; Candra Dewi; Randy Cahya Wihandika (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Multiple salesman problem (M-TSP) is an advanced problem from TSP that is looking for minimal cost from tour in some location which can only be visited once. There are many problems that are included in the case of M-TSP, one of them is the passenger pickup route. Choosing the right path in the process of picking up passengers will certainly affect the effectiveness and cost in those activities. Ant colony optimization (ACO) is an algorithm that adopts the intelligence of a group of ants in a food search and able to solving the M-TSP problem. In this study there are two parameters used in finding the best solution that is distance and time. In equalize the value of distance and time parameters, applied min-max normalization in data. The best results are obtained when the parameter NcMax or iteration is 300, the value of Î± is 0.5, the value of Î² is 0.5, the value of Ï„0 is 0.5, the value of Ï is 0.5 and the number of passengers in one car as much as 5 with cost 148.829.